Efficient fabrication of high‐capacity immobilized metal ion affinity chromatographicmedia: The role of the dextran‐grafting process and its manipulation. Issue 6 (March 2016) - Zhao, Lan; Zhang, Jingfei; Huang, Yongdong; Li, Qiang; Zhang, Rongyue; Zhu, Kai; Suo, Jia; Su, Zhiguo; Zhang, Zhigang; Ma, Guanghui
Abstract : J. Sep. Sci. 2016, 39, 1130–1136 DOI: 10.1002/jssc.201501291 A novel high‐capacity Ni 2+ immobilized metal ion affinity chromatographic medium was prepared through dextran‐grafting process. The dextran‐grafting degree of the media had a great effect on His‐tagged protein binding performance. The maximum binding capacity was obtained as a certain thickness of dextran was grafted.